Agitator design for gas-liquid fermenters and bioreactors - Benz, Gregory T. (John Wiley & Sons, Inc., 2021)
"As in all kinds of process equipment, agitators must be correctly sized to deliver the process function, while maximizing return on investment and minimizing total energy cost. In a bioreactor, agitators are one of the prime drivers for promoting the development of gas/liquid interfacial area, which has a direct impact on mass transfer and hence production rate. Power consumption is a significant cost, which can be minimized by proper design of the agitation and air delivery systems. Finally, downtime is very expensive, so mechanically reliable agitators are essential. This book is an invaluable guide to the initiation, installation, and maintenance of agitators in fermenters and bioreactors"--